Grasshopper Meal (Ornithacris cavroisi) in Broiler Diets in Niger: Bioeconomic Performance - BRAH, Nouri; HOUNDONOUGBO, M. FRÉDÉRIC; ISSA, SALISSOU (My University, 2018)
Objective: This study was conducted to evaluate the bioeconomic performance of grasshopper meal (GM) when used to replace fish meal (FM) in broiler diets during a period of 49 days. Materials and Methods: A total of 360 one-day-old broiler chicks (Cobb 500) were used in this experiment. The FM was replaced with GM on a kg per kg basis at 0% (control), 25% (25% GM+75% FM), 50% (50% GM+50% FM), 75% (75% GM+25% FM) and 100% (100% GM+0% FM) in broiler diets. Treatments (G0, G25, G50, G75 and G100) were randomly distributed into 20 pens of 18 birds each with 4 replications (4 pens/treatment). Data were analyzed in R 3.2 using ANOVA and regression was executed in Microsoft Excel 2013. Results: At the end of the experiment, the daily feed intake, body weight and weight gain linearly and significantly decreased (p<0.05) with increasing substitution rates of fish meal with grasshopper meal. Also, the results showed that feed conversion ratios linearly increased and were significantly affected by the treatments (p<0.05), with the highest performance observed in broilers fed the control diet. Carcass characteristics also significantly decreased (p<0.05) with increasing levels of grasshopper meal in broiler diets. However, the substitution did not significantly affect feed efficacy of broilers during the growing phase (p>0.05). In addition, during the 49 days of experimentation, the body weight, feed conversion ratio, economic feed efficiency and carcass yield of broilers fed G0, G25 and G50 were similar (p>0.05). Conclusion: Therefore, in Niger, fish meal may be substituted with up to 50% grasshopper meal in broiler feed.
Keywords: Bioeconomic performance; broiler; fish meal; grasshopper meal; Niger; protein